The Effects of Home Computers on Educational Outcomes: Evidence from a Field Experiment with Community College Students - Robert W. Fairlie; Rebecca A. London (Center for Economic Studies and ifo Institute (CESifo), 2013)
There is no clear theoretical prediction regarding whether home computers are an important input in the educational production function. To investigate the hypothesis that access to a home computer affects educational outcomes, we conduct the first-ever field experiment involving the provision of free computers to students for home use. Financial aid students attending a large community college in Northern California were randomly selected to receive free computers and were followed for two years. Although estimates for a few measures are imprecise and cannot rule out zero effects, we find some evidence that the treatment group achieved better educational outcomes than the control group. The estimated effects, however, are not large. We also provide some evidence that students initially living farther from campus benefit more from the free computers than students living closer to campus. Home computers appear to improve students' computer skills and may increase the use of computers at non-traditional times. The estimated effects of home computers on educational outcomes from the experiment are smaller than the positive estimates reported in previous studies. Using matched CPS data, we find estimates of educational effects that are considerably larger than the experimental estimates.
Keywords: J24; 330; technology; computers; community college; education